2012
DOI: 10.1007/s00406-012-0350-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between fully automated MRI-based volumetry of different brain regions and neuropsychological test performance in patients with amnestic mild cognitive impairment and Alzheimer’s disease

Abstract: Fully automated magnetic resonance imaging (MRI)-based volumetry may serve as biomarker for the diagnosis in patients with mild cognitive impairment (MCI) or dementia. We aimed at investigating the relation between fully automated MRI-based volumetric measures and neuropsychological test performance in amnestic MCI and patients with mild dementia due to Alzheimer's disease (AD) in a cross-sectional and longitudinal study. In order to assess a possible prognostic value of fully automated MRI-based volumetry for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 15 publications
7
28
2
3
Order By: Relevance
“…Chronic hypoxemia is a major mechanism that can adversely affect cognitive performance and hippocampal volume [27-30]. In this study, we also examined the relationships between hippocampal volume and relevant factors in mild-to-moderate and severe COPD groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxemia is a major mechanism that can adversely affect cognitive performance and hippocampal volume [27-30]. In this study, we also examined the relationships between hippocampal volume and relevant factors in mild-to-moderate and severe COPD groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Arlt and colleagues have shown that loss of GM in the left hippocampus is correlated with poorer performance on the Boston Naming Test, MiniMental Status Examination, and trail-making test B in aMCI over time [30] . Notably, although these studies used different analysis techniques and follow-up times (1, 2, 3, or 6 years), they consistently indicate that the hippocampal atrophy is greater in aMCI converters than non-converters, and further suggest that hippocampal subregions, especially CA1 and the subiculum, can better predict the conversion of aMCI to AD.…”
mentioning
confidence: 99%
“…Recent reviews have yielded evidence supporting the existence of noun naming deficits in individuals with MCI [10,14]. However, individual studies have revealed contradictory results: while some studies suggest that individuals with MCI performed significantly more poorly on the BNT than HE subjects [4,5,6,7,8,9,11,12,13], other studies did not find significant differences between the two groups [10,25,26,27,28,29,30,31,32]. These inconsistent reports about the performance on BNT in MCI can be explained by differences in the diagnostic criteria, procedural differences in the naming tasks, and the possibility that only a segment of patients with MCI has naming deficits [33].…”
Section: Introductionmentioning
confidence: 94%